Analisis Keterlambatan pada Proyek Peningkatan Gedung Kantor DPU Kota Balikpapan Menggunakan Lean Six Sigma Framework - Hesra Bunga; Gunaedy Utomo; Reno Pratiwi (Jurnal Talenta Sipil, 2026)
Construction project delays are a common problem that can have a significant impact on time efficiency, costs, and the quality of work. Therefore, a systematic and data-driven management approach is needed to identify the main causes of delays and determine the appropriate improvement strategies. This study aims to analyze the factors causing delays in the Balikpapan City Public Works Office (DPU) building improvement project using the Lean Six Sigma approach through the Define, Measure, Analyze, Improve, and Control (DMAIC) stages. The research data was obtained from project documents, field observations, interviews, and questionnaires administered to workers and project supervisors. The analysis was conducted using Pareto charts, comparisons of planned and actual workforce allocations, and fishbone diagrams to identify the root causes of delays. The results of the study show that the dominant factors causing project delays are human resources aspects, particularly the mismatch between the number of workers available and the work requirements in a given period, as well as the transfer of workers to other projects. Meanwhile, factors such as machinery, work methods, materials, and environmental conditions were not found to have a significant impact on project delays, as most were considered to be in fairly good condition and did not hinder the work process. Based on the results of this analysis, the recommended improvement strategies include improving worker attendance monitoring, adjusting worker allocation according to the needs of each stage of the project, and recruiting additional workers during periods of high workload